Latest News on Arabidopsis Brassinosteroid Perception and Signaling - Harter, Klaus; Witthöft, Janika (Frontiers in Plant Science, 2011)
Brassinosteroids (BRs) are plant hormones regulating growth and development. In interaction with other hormones, they are involved in environmental cue responses. The present model of the BR response pathway in Arabidopsis includes the perception of the hormone by the plasma membrane (PM) receptor brassinosteroid insensitive 1 (BRI1) and its hetero-oligomerization with the co-receptor BRI1-associated receptor kinase 1 (BAK1), followed by the activation of a signaling-cascade finally resulting in the expression of BR-responsive genes. New findings have shed light on the receptor density in the PM and on the molecular mechanism of BR perception, which includes the hormone-induced formation of a platform in the BRI1 extracellular domain for interaction with BAK1. Furthermore, new knowledge on early, BRI1-initiated signaling events at the PM–cytoplasm interface has recently been gained. In addition, a fast BR response pathway that modifies the membrane potential and the expansion of the cell wall – both crucial processes preceding cell elongation growth – have been identified. In this review, these latest findings are summarized and discussed against the background of the present model of BRI1 signaling.